2018
DOI: 10.5194/se-2018-63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oblique rifting: the rule, not the exception

Abstract: Abstract. Movements of tectonic plates often induce oblique deformation at divergent plate boundaries. This is in striking contrast with traditional conceptual models of rifting and rifted margin formation, which often assume 2D deformation 10 where the rift velocity is oriented perpendicular to the plate boundary. Here we quantify the validity of this assumption by analysing the kinematics of major continent-scale rift systems in a global plate tectonic reconstruction from the onset of Pangea breakup until pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 105 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…Our analysis of thermochronometric data and magmatism patterns within the RGR rules out rift models involving time progressive propagation of rifting (northward propagation in the case of the RGR). Accordingly, we consider generalized synchronous rifting models—block rotation and oblique strain, as possible mechanisms driving the development of the RGR (Figure ; e.g., Ebinger et al, ; Nelson et al, ; Brune et al, ; Molnar et al, ; Brune et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our analysis of thermochronometric data and magmatism patterns within the RGR rules out rift models involving time progressive propagation of rifting (northward propagation in the case of the RGR). Accordingly, we consider generalized synchronous rifting models—block rotation and oblique strain, as possible mechanisms driving the development of the RGR (Figure ; e.g., Ebinger et al, ; Nelson et al, ; Brune et al, ; Molnar et al, ; Brune et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…However, this rotation is suggested to have occurred in the middle to late Miocene (i.e., 10–15 Myr after rift initiation as determined by our thermochronometric data analysis). Therefore, we cannot rule out an oblique strain model especially in light of a recent global rifting study which showed that the majority of rifting is accomplished from oblique strain (Brune et al, ). We suggest that rifting is driven by a combination of oblique strain and block rotation, mechanisms which evolve with the changing far‐field plate boundary conditions through time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transform faults and systems can become particularly complex when the relative motion of the plates either side changes (Farangitakis et al, 2019), or a component of compression or extension is present, resulting in the development of transpressional and Manuscript under review for Interpretation transtensional systems . In addition to true transform faults and systems, it has been shown that the majority of rifts preceding conjugate margin formation can be considered to be oblique, lying on a spectrum between truly orthogonal rifts and transform-type margins (Brune et al, 2018). Spreading on mid-ocean ridges can also be oblique, and vary through the lifespan of a ridge, such as on the Reykjanes Ridge (Martinez et al, 2019), again complicating plate tectonic reconstructions, and conjugate margin studies.…”
Section: Transforms Oblique Rifting and Spreadingmentioning
confidence: 99%
“…In addition, transform faults and systems can become particularly complex when the relative motion of the plates either side changes (Farangitakis et al, 2019), or a component of compression or extension is present, resulting in the development of transpressional and Manuscript under review for Interpretation transtensional systems (Peace et al, 2018b). In addition to true transform faults and systems, it has been shown that the majority of rifts preceding conjugate margin formation can be considered to be oblique, lying on a spectrum between truly orthogonal rifts and transform-type margins (Brune et al, 2018). Spreading on mid-ocean ridges can also be oblique, and vary through the lifespan of a ridge, such as on the Reykjanes Ridge (Martinez et al, 2019), again complicating plate tectonic reconstructions, and conjugate margin studies.…”
Section: Transforms Oblique Rifting and Spreadingmentioning
confidence: 99%